Increasing Academic Achievement through Madrasah Principal Strategies - Murni Murni; Nanda Saputra (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
Strategy is a procedure used to carry out an activity to achieve madrasah goals. In carrying out the leadership process, the head of the madrasah certainly has strategies that will be carried out as a leader in the madrasah for improving student achievements to become an indicator of the success of managing the madrasah. This research aims to find out how the madrasa head's strategy, and the implementation of the madrasa head's strategy in improving the academic achievement of students at MA Unggulan XYZ Jombang. This research uses a qualitative approach with a case study type of research and is descriptive in nature with subjects namely the head of the madrasah, head of curriculum, and also teachers. The data collection techniques used were observation, interviews, and documentation studies. The validity of the data was tested by triangulating sources and techniques. The data obtained was analyzed through data reduction, data presentation, and data verification. The results of this research show that 1) the madrasa head's strategy in improving students' academic achievement by supervising, sector reading, boosting six superior madrasa programs, and also giving appreciation to students who excel in the form of free tuition fees for one semester 2) implementation of the madrasa head's strategy in improving Students' academic achievements are carried out by holding sectoral reding evaluation meetings by communicating with each other with sectoral readings.